The Impact of The Change in Accounting Policy on Banking Credit in Light of The Financial Crisis - Sirwan Lutfulah Abdulla; Hemn Mahamad Aziz; Rizgar Ali Ahmad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Accounting policy considered as a section of strategic planning for labour organizations in general and more particularly financial organizations, so it’s important to be concerned in order to control the organizations activities. The significant of this research comes after selecting and implementing the best available accounting policies inside commercial banks in Kurdistan Region for the sake of continuing banks credits and their financial situation during financial crisis. This research aims to understand the impact of available accounting policies inside Kurdistan Region’s commercial banks on credit decisions for credit seeking companies, then to identify the importance of credit follow-up after granting them in order to achieve customer continuity for paying back instalments with the interest amount based on the bond’s conditions. To achieve this, 62 questionnaires have been created and distributed among (general directors, assistant managers, head of departments, head of units, and more precisely heads of accounting and auditing departments). Afterward, the data has been analysed by (SPSS 22.0) via statistical tools and regression analysis. The research reached a bunch of results, such as; the possible accounting policies that is implemented in banks as a base of accounting treatments, or to adjust illustrated accounting information inside financial statements within one of credit banks indicators, which is known as granting bank credit, is considered as one of the hardest decisions that banks responsible for it especially during financial crisis. Finally, the research is concluded with some recommendations, in the foreground accounting policy disclosure because it affects positively on bank credit decisions, then the necessity of holding training and qualification courses for accountants in financial management for the right use of accounting policy